(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The role of language learning competencies is vital in a second language acquisition. Also, the individual characteristics of learner, such as extrovert or introvert, can require from educator to modify the ways of conducting lessons and lesson plan